The Effect of Isometric Handgrip Exercise Therapy on Reducing Blood Pressure in Hypertension Patient - Kusniawati; Salma Yufliah (CV. CENDIKIA JENIUS INDONESIA, 2025)
Background: Hypertension is systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. One of the triggers for hypertension is lack of physical activity. Efforts to prevent and treat hypertension can be done with pharmacological and non-pharmacological therapy. One of the non- pharmacological therapis that can be carried out is isometric handgrip exercise. The aim is to determine the effect of isometric handgrip exercise therapy on blood pressure in hypertensive patients. Method: quasi-experimental with a one group pretest-posttest design research approach. The number of samples taken was 15 respondents with a non-probability sampling technique using purposive sampling. The instruments for this research are Isometric handgrip exercise therapy SOP, Isometric therapy observasion sheet, blood pressure record sheet, sphygmomanometer and stethoscope. Bivariate analysis uses the dependent T test if the data is normally distributed. Results the average post-test diastole was 80.93. The results of the dependent study showed differences before and after isometric handgrip exercise therapy on blood pressure with p value = 0.000 (α < 0,05). Conclusion: The results of this research are used as evidence-based and complementary therapy in the management of hypertension sufferers to reduce blood pressure independently.